Design principles as bridge between scientific knowledge production and practice design - Euler, Dieter (EDeR. Educational Design Research, 2017)
This paper uses design-based research (DBR) to describe an approach that combines scientific knowledge production with the development of innovative practice concepts. The DBR research process begins with the following question: How can an aspired, initially vaguely formulated goal be reached by a yet to be developed design? As the research process progresses, interventions are developed, tested in the field, and evaluated. This process generates increasingly stable practice concepts for reaching the aspired goals through several iterative cycles and statements about the effectiveness of the intervention’s supporting pillars based on theoretical and empirical research. These statements are developed in the form of design principles. In this paper, we describe the characteristics that constitute design principles and how they emerge within a DBR research process.